Barriers to recombination between closely related bacteria: MutS and RecBCD inhibit recombination between Salmonella typhimurium and Salmonella typhi - Zahrt, Thomas C. (The National Academy of Sciences of the USA, 1997)
Previous studies have shown that inactivation of the MutS or MutL mismatch repair enzymes increases the efficiency of homeologous recombination between Escherichia coli and Salmonella typhimurium and between S. typhimurium and Salmonella typhi. However, even in mutants defective for mismatch repair the recombination frequencies are 10(2)- to 10(3)-fold less than observed during homologous recombination between a donor and recipient of the same species. In addition, the length of DNA exchanged during transduction between S. typhimurium and S. typhi is less than in transductions between strains of S. typhimurium. In homeologous transductions, mutations in the recD gene increased the frequency of transduction and the length of DNA exchanged. Furthermore, in mutS recD double mutants the frequency of homeologous recombination was nearly as high as that seen during homologous recombination. The phenotypes of the mutants indicate that the gene products of mutS and recD act independently. Because S. typhimurium and S. typhi are ≈98–99% identical at the DNA sequence level, the inhibition of recombination is probably not due to a failure of RecA to initiate strand exchange. Instead, these results suggest that mismatches act at a subsequent step, possibly by slowing the rate of branch migration. Slowing the rate of branch migration may stimulate helicase proteins to unwind rather than extend the heteroduplex and leave uncomplexed donor DNA susceptible to further degradation by RecBCD exonuclease.